2019
DOI: 10.1098/rspb.2019.1698
|View full text |Cite
|
Sign up to set email alerts
|

Is there an oxidative cost of acute stress? Characterization, implication of glucocorticoids and modulation by prior stress experience

Abstract: Acute rises in glucocorticoid hormones allow individuals to adaptively respond to environmental challenges but may also have negative consequences, including oxidative stress. While the effects of chronic glucocorticoid exposure on oxidative stress have been well characterized, those of acute stress or glucocorticoid exposure have mostly been overlooked. We examined the relationship between acute stress exposure, glucocorticoids and oxidative stress in Japanese quail (Coturnix japonica). We (i) characterized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Also, retrospective data derived from AE-IPF patients treated with corticosteroid alone did not show any reduction in mortality rate over the short term [ 39 ]. Several evidence in the animal models suggest that corticosteroid exposure can cause to increase oxidative stress [ 40 , 41 ]. Although the exact mechanism by which corticosteroid increase oxidative stress is not well known, several hypothesis have been reported that glucocorticoids could bind to mitochondrial glucocorticoid receptors and activate mitochondrial function to generate ROS or ROS is generated by the activation of the protein kinase C (PKC) β / p66 shc signaling pathway by glucocorticoid in the cell [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, retrospective data derived from AE-IPF patients treated with corticosteroid alone did not show any reduction in mortality rate over the short term [ 39 ]. Several evidence in the animal models suggest that corticosteroid exposure can cause to increase oxidative stress [ 40 , 41 ]. Although the exact mechanism by which corticosteroid increase oxidative stress is not well known, several hypothesis have been reported that glucocorticoids could bind to mitochondrial glucocorticoid receptors and activate mitochondrial function to generate ROS or ROS is generated by the activation of the protein kinase C (PKC) β / p66 shc signaling pathway by glucocorticoid in the cell [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several evidence in the animal models suggest that corticosteroid exposure can cause to increase oxidative stress [ 40 , 41 ]. Although the exact mechanism by which corticosteroid increase oxidative stress is not well known, several hypothesis have been reported that glucocorticoids could bind to mitochondrial glucocorticoid receptors and activate mitochondrial function to generate ROS or ROS is generated by the activation of the protein kinase C (PKC) β / p66 shc signaling pathway by glucocorticoid in the cell [ 40 , 41 ]. Therefore, in patients with ARDS and AE-ILDs, the use of corticosteroids may be harmful from the point of view of oxidative stress increase, and the potential antioxidant treatment such as N-acetylcysteine needs to be examined in the future [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase of glucocorticoids in the blood stream after aggressive interactions has been reported both in seasonally territorial [e.g., 69] and year-round territorial vertebrates [70,71]. Further, a direct link between glucocorticoids and oxidative stress has previously been reported [7275], and females seem to be more susceptible to the effects of glucocorticoids on oxidative stress than males [reviewed by 73, but see 76]. Thus, the interaction between glucocorticoids and oxidative status could provide an alternative explanation of our results that we cannot resolve at the moment: aggression may lower OXY concentrations directly as a consequence of an increased metabolism or indirectly via an increase in glucocorticoid concentration, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Also, retrospective data derived from AE-IPF patients treated with corticosteroid alone did not show any reduction in mortality rate over the short term (39). Several evidence in the animal models suggest that corticosteroid exposure can cause to increase oxidative stress (40,41). Although the exact mechanism by which corticosteroid increase oxidative stress is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism by which corticosteroid increase oxidative stress is not well known. several hypothesis have been reported that glucocorticoids could bind to mitochondrial glucocorticoid receptors and activate mitochondrial function to generate ROS or ROS is generated by the activation of the protein kinase C (PKC) β / p66 shc signaling pathway by glucocorticoid in the cell (40,41). Therefore, in patients with ARDS and AE-ILDs, the use of corticosteroids may be harmful from the point of view of oxidative stress increase, and the potential antioxidant treatment such as N-acetylcysteine needs to be examined in the future (42).…”
Section: Discussionmentioning
confidence: 99%